Cloudy - Lee, Ryan Zhaoheng (Nanyang Technological University, 2023)
This report serves as a main documentation of the work in progress until the final look and outcome of the film “Cloudy”. The report will also cover the technical and artistic aspects and difficulties of the project during the production stages.